Fn14 Promotes Differentiation of Human Mesenchymal Stem Cells into Heart Valvular Interstitial Cells by Phenotypic Characterization. Issue 5 (May 2014) - Huang, Wei; Xiao, Ding‐Zhang; Wang, Yigang; Shan, Zhi‐Xin; Liu, Xiao‐Ying; Lin, Qiu‐Xiong; Yang, Min; Zhuang, Jian; Li, Yangxin; Yu, Xi‐Yong
<x xml:space="preserve">Abstract</x> Despite the fact that tissue engineered heart valves (TEHV) hold great promise for heart valve disease treatment, one of the challenges is to find suitable seeding cells. Bone marrow derived mesenchymal stem cells (MSCs) were considered to be one of the best seed cell sources. In this study we propose a novel approach to promote stem cell differentiation into the seed cells of TEHV, valvular interstitial cells (VICs). Newly induced MSCs (iMSCs) were created from a co‐culture niche in which healthy human donor derived MSCs were co‐cultured with cardiac fibroblasts (H9C2 cell line). Then iMSCs were transfected with either a mock vector (iMSCsmock) as controls or with a vector that overexpresses thefibroblast inducible factor 14 (Fn14) gene (iMSCsFn14). Immunofluorescence staining was performed to assay VIC differentiation. Western blot analysis was performed to analyze the involved signaling pathway. The results demonstrate that the expression of α‐smooth muscle actin (SMA) was significantly higher in iMSCsFn14 as compared with iMSCmock, and MSC, and also had higher co‐alignment of α‐actinin and stress fiber (F‐actin) in bundles. Additionally, increased biosynthesis of extracellular matrix (ECM) proteins including collagen I, collagen III, and fibronection were observed in iMSCsFn14 in comparison with iMSCsmock. These data observed in iMSCsFn14 were in accordance with VIC phenotype from normal heart valves. In addition, the PI3K/Akt signaling pathway was activated in iMSCsFn14 which allowed higher Akt phosphorylation (p‐Akt) levels and SMA levels, whereas, it was attenuated by LY294002 (PI3K/Akt inhibitor). These new findings of the effect of Fn14 on VIC‐like cell differentiation may provide a novel therapeutic strategy for heart valve disease treatment. J. Cell. Physiol. 229: 580–587, 2014. © 2013 Wiley Periodicals, Inc.